2019
DOI: 10.1038/s42005-019-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Single plasmon hot carrier generation in metallic nanoparticles

Abstract: Hot carriers produced from the decay of localized surface plasmons in metallic nanoparticles are intensely studied because of their optoelectronic, photovoltaic and photocatalytic applications. From a classical perspective, plasmons are coherent oscillations of the electrons in the nanoparticle, but their quantized nature comes to the fore in the novel field of quantum plasmonics. In this work, we introduce a quantum-mechanical material-specific approach for describing the decay of single quantized plasmons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…This is a consequence of the large matrix elements for transitions between states that are close to the Fermi energy, see Eq. (19), which is also consistent with the trends observed in time-dependent DFT calculations [34]. Similarly to the d-to-sp case, the curves exhibit a peak when the photon energy is sufficiently large to excite a localized surface plasmon, see inset of Fig.…”
Section: Materials Parameterssupporting
confidence: 88%
“…This is a consequence of the large matrix elements for transitions between states that are close to the Fermi energy, see Eq. (19), which is also consistent with the trends observed in time-dependent DFT calculations [34]. Similarly to the d-to-sp case, the curves exhibit a peak when the photon energy is sufficiently large to excite a localized surface plasmon, see inset of Fig.…”
Section: Materials Parameterssupporting
confidence: 88%
“…[ 1,3,4,6,12–27 ] To promote the generation of hot carriers with applications in photovoltaics, photodetection, and photoelectrochemical devices, pioneering studies demonstrated the key role that localized surface plasmon resonance (LSPR) plays in hot‐electron‐based energy conversion. [ 6,9,12,28–32 ] It has been established that the LSPR‐driven hot carriers expand the boundary of performance of efficient near‐infrared (NIR) detection of silicon‐based photodiodes, [ 21 ] improve photoconversion efficiency, [ 20,33,34 ] and enhance selectivity for CO production over hydrogen evolution. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…We have studied hot-carrier properties of embedded spherical silver nanoparticles consisting of between 68 and 254 atoms corresponding to diameters between 1.08 and 2.10 nm. To calculate hot-carrier distributions in these systems, we extended the approach developed in ref ( 22 ) for alkali metal nanoparticles. Following this approach, the decay of the localized surface plasmon (LSP) into a single electron-pair is considered.…”
Section: Resultsmentioning
confidence: 99%
“… 26 The TDDFT calculations were carefully converged with respect to the number of empty states. Note that our framework includes a quantized treatment of the plasmon, relevant to describe quantum effects present in small nanoparticles and/or when a low density of plasmons are excited as introduced in ref ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation